External knowledge search paths in open innovation processes of small and medium enterprises. Issue 3 (25th November 2019) - Chaochotechuang, Preecha; Daneshgar, Farhad; Mariano, Stefania
Abstract : Purpose: The purpose of this paper is to advance knowledge by exploring how small and medium enterprises (SMEs) search for external knowledge in their open innovation processes, and how the search can be advanced. Design/methodology/approach: This exploratory research employs a qualitative multiple case study design. A literature review of open innovation in SMEs and external knowledge search is used to build the premises of this study. Semi-structured interviews with eight SMEs are employed to collect subsequent exploratory empirical data. Findings: This exploratory study revealed that SMEs adopted a combination of cognitive and experiential search heuristics where cognitive search was practiced during the innovation research process when searching for external knowledge, whilst experiential search was practiced during the innovation development process. Concerning the search space, this study found that SMEs mainly explored local knowledge, and occasionally pursued distant knowledge when confronted with complex problems. The reason for the above behavior was explained to be related to the reduction of costs and risks associated with innovation activities. Originality/value: External knowledge plays a pivotal role in open innovation. Although extant studies have shed some light on how large firms search for external knowledge, however, it is not clear how SMEs search for external knowledge. Moreover, this study focuses on learning about both the search space and the search heuristics at both the research and the development stages of the innovation process.